Wangaratta, Victoria, 1994 - De Berquelle, Raymond 1933- (1994)
Street scenes and buildings in Wangaratta, Victoria.
Regional cities and major towns project.
P910/1-24.
Images individually catalogued and digitised.
Also available online
List available (1 p.)
Keywords: Wangaratta (Vic.) -- Photographs